2012
DOI: 10.1371/journal.pone.0037378
|View full text |Cite
|
Sign up to set email alerts
|

Shifting the Paradigm: The Putative Mitochondrial Protein ABCB6 Resides in the Lysosomes of Cells and in the Plasma Membrane of Erythrocytes

Abstract: ABCB6, a member of the adenosine triphosphate–binding cassette (ABC) transporter family, has been proposed to be responsible for the mitochondrial uptake of porphyrins. Here we show that ABCB6 is a glycoprotein present in the membrane of mature erythrocytes and in exosomes released from reticulocytes during the final steps of erythroid maturation. Consistent with its presence in exosomes, endogenous ABCB6 is localized to the endo/lysosomal compartment, and is absent from the mitochondria of cells. Knock-down s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 63 publications
7
91
0
1
Order By: Relevance
“…Lan blood group mismatch can cause hemolytic transfusion reactions and hemolytic disease of the newborn. Kiss [20] recently confirmed ABCB6 as a glycoprotein present in the membrane of mature erythrocytes and in exosomes released from re- Figure 2. 3D structure models of ABCB6 in inward conformation.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Lan blood group mismatch can cause hemolytic transfusion reactions and hemolytic disease of the newborn. Kiss [20] recently confirmed ABCB6 as a glycoprotein present in the membrane of mature erythrocytes and in exosomes released from re- Figure 2. 3D structure models of ABCB6 in inward conformation.…”
Section: Discussionmentioning
confidence: 91%
“…The previous results demonstrated that ABCB6 is expressed in RBCs and during erythroid differentiation of K562 cells [20,21]. We examined ABCB6 expression and localization in an ex vivo model of erythroid differentiation.…”
Section: Abcb6 Expression During Erythroid Differentiationmentioning
confidence: 95%
See 2 more Smart Citations
“…57 Moreover, in erythrocyte membranes it bears the Langereis (Lan) blood group antigen system. 58,59 ABCB6 expression increases during erythroid differentiation of CD34+ cells. 56 The ABCB6 missense mutations in FP does not alter mRNA or protein levels, or subcellular localization in mature erythrocytes or erythroid precursor cells, but are predicted to have a pathogenic consequence on protein function.…”
Section: Familial Pseudohyperkalemia and Cryohydrocytosismentioning
confidence: 99%